Introduction to communication studies - Fiske, John.; Jenkins, Henry (London [Eng.] : Routledge, 2011)
This revised edition of a now classic text includes a new introduction by Henry Jenkins, explaining 'Why Fiske Still Matters' for today's students, followed by a discussion between former Fiske students Ron Becker, Elana Levine, Darrell Newton and Pamela Wilson on the theme of 'Structuralism and Semiotics, Fiske-Style'. Both underline the continuing relevance of this foundational text in communication studies.
1. Communication theory -- 2. Other models -- 3. Communication, meaning, and signs -- 4. Codes -- 5. Signification -- 6. Semiotic methods and applications -- 7. Structuralist theory and applications -- 8. Empirical methods -- 9. Ideology and meanings.
Includes bibliographical references.
Mode of access: World Wide Web.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Communication; Semiotics; Electronic books